ANALISIS PENGARUH FLEKSIBILITAS KERJA DAN WORK-LIFE BALANCE TERHADAP KEPUASAN KERJA KARYAWAN GENERASI Z DI KOTA BANDAR LAMPUNG - Ardansyah; Maulana Fadil Rachman (Program Studi Manajemen | Universitas Pasir Pengaraian, 2025)
The purpose of this study was to collect data on the perspectives of Generation Z workers in Bandar Lampung City regarding the work-life balance and flexibility offered by their profession. Millennials and members of Generation Z strongly support work-life balance and flexibility in the workplace as methods to increase job satisfaction. This study uses a multiple linear regression approach to measure job satisfaction as the dependent variable, with work-life balance and flexibility as the independent variables that influence it. The city of Bandar Lampung selected 100 employees from Generation Z to participate in this research. Based on the results of the regression analysis, both work-life balance (X2) and work flexibility (X1) demonstrated a meaningful and positive influence on job satisfaction, with correlation coefficients of r = 0.421 (p = 0.003) and r = 0.965 (p = 0.000), respectively. Furthermore, with a p-value of 0.000 and an F-statistic value of 97.317, no additional variables were identified as having a notable impact on the outcomes. As a result of greater leeway in scheduling and other work-related factors, members of Generation Z report higher levels of job satisfaction. If companies truly care about the happiness and productivity of their employees, they will create policies that encourage both.